THE GENRE OF LANDSCAPE IN FINE ART AND ITS SPECIFIC ASPECTS - Abdukakhorova Muslima Mirzabakhrom Qizi (Western European Studies, 2024)
This article discusses views on the genre of landscape in the science of color images. The necessary information is provided on specific aspects of painting, genres and the expression of color in them. In addition, there are ideas about the proportions of natural landscapes, the disclosure of composition and the use of hot and cold colors, as well as information about artists who worked in the landscape genre
Keywords: Genre; perspective; composition